2019
DOI: 10.1097/md.0000000000016022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of early postoperative recovery between laryngeal mask airway and endotracheal tube in laparoscopic cholecystectomy

Abstract: Background: Laryngeal mask airway (LMA) insertion provokes fewer stress responses than endotracheal intubation. This study aimed to evaluate the LMA Protector for assessing improvements in intraoperative hemodynamic stability and to reduce postoperative discomfort compared with endotracheal intubation in laparoscopic cholecystectomy. Methods: Fifty-six patients who underwent laparoscopic cholecystectomy while under sevoflurane-based general anesthesia were randomly allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…14 In noncardiac procedures, when compared with ETT, SGA use also has been shown to decrease the incidence of laryngospasm during emergence from anesthesia and reduced incidence of postoperative hoarse voice, sore throat, nausea, pain, and coughing. [15][16][17][18] Laryngeal mask airway devices also have been shown to induce smaller catecholamine and mean arterial pressure responses in patients undergoing bariatric surgery. 19 In addition, multiple recent studies have demonstrated the robust safety profile of TEE performed with an SGA rather than the traditional ETT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In noncardiac procedures, when compared with ETT, SGA use also has been shown to decrease the incidence of laryngospasm during emergence from anesthesia and reduced incidence of postoperative hoarse voice, sore throat, nausea, pain, and coughing. [15][16][17][18] Laryngeal mask airway devices also have been shown to induce smaller catecholamine and mean arterial pressure responses in patients undergoing bariatric surgery. 19 In addition, multiple recent studies have demonstrated the robust safety profile of TEE performed with an SGA rather than the traditional ETT.…”
Section: Discussionmentioning
confidence: 99%
“…GA using a supraglottic airway (GA-SGA) has emerged as a promising alternative to MAC or GA with an ETT (GA-ETT) for TF-TAVR. 14 Studies in noncardiac populations previously have demonstrated benefits of an SGA relative to an ETT in factors such as operating room time, 14 sore throat, 15 desaturation, 16 airway complications, 17 early recovery, 18 and catecholamine and hemodynamic responses. 19 The aim of the present study was to compare outcomes of TF-TAVR at a single institution using GA-SGA for airway maintenance versus MAC.…”
mentioning
confidence: 99%
“…In patients under general anesthesia, laryngeal mask airway (LMA) method is used as an alternative to endotracheal intubation to maintain the airway, and its use had been increased. The LMA method was designed in 1981 and is superior to ETT in terms of no tracheal damage during insertion and removal of the tube, less airway stimulation, less invasion of airway tissue, easier implantation and airway establishment [ 12 , 13 ]. Relative to endotracheal intubation, LMA has greater incidence of sore throat, however the intensity of sore throat may be mild and might not affect the choice of LMA [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this multicenter study, we further investigated the effectiveness and safety of LMA® Protector™ in laparoscopic surgeries in a large sample and intended to provide evidence for LMA to be used in laparoscopic surgery. (3,16)…”
Section: Introductionmentioning
confidence: 99%